Cobalt phosphide nanoarrays on a borate-modified nickel foam substrate as an efficient dual-electrocatalyst for overall water splitting - Zhou, Ruijuan; Zhang, Jinghao; Long, Junxi; Li, Lingfeng; Ye, Qinglan; Xu, Xuetang; Wang, Fan (Journal of colloid and interface science, 2025)
[Display omitted] Developing efficient non-noble metal dual-functional electrocatalysts for overall water splitting is essential for the production of green hydrogen. Given the significant advantages of self-supporting electrodes, regulating the growth of self-supporting nanoarrays on a conductive substrate is conducive to improving the electrocatalytic activity. In this work, aligned cobalt phosphide (CoP) nanowire arrays grown on borate-modified Ni foam substrate (CoP/R-NF) were utilized as a bifunctional electrocatalyst for both hydrogen evolution reactions (HER) and oxygen evolution reactions (OER) in alkaline solution. The borate interfacial layer regulated the growth behavior of CoP nanowires, promoting a tip-enhanced electric field effect, facilitating an enhanced bimetallic synergistic effect. The CoP/R-NF electrode showed substantial catalytic activity for HER (η10 = 35 mV, 70 mV dec-1) and OER (241 mV, 32 mV dec-1). Moreover, a low cell voltage of 1.50 V to drive 10 mA cm−2 current density for overall water-splitting was achieved in an alkaline water electrolyzer, with long-term durability of 200 h at 100 mA cm−2, indicating the potential application of CoP/R-NF as a bifunctional catalyst for clean and renewable energy utilization. Such a synthetic strategy could pave the way for the development of non-noble bifunctional electrocatalysts for comprehensive water splitting.